Ostracism and theft in heterogeneous groups - Baier, Alexandra,Balafoutas, Loukas,Jaber-Lopez, Tarek (Research platform Empirical and Experimental Economics, University of Innsbruck, 2021)
Ostracism, or exclusion by peers, has been practiced since ancient times as a severe form of punishment against transgressors of laws or social norms. The purpose of this paper is to offer a comprehensive analysis on how ostracism affects behavior and the functioning of a social group. We present data from a laboratory experiment, in which participants face a social dilemma on how to allocate limited resources between a productive activity and theft, and are given the opportunity to exclude members of their group by means of majority voting. Our main treatment features an environment with heterogeneity in productivity within groups, thus creating inequalities in economic opportunities and income. We find that exclusion is an effective form of punishment and decreases theft by excluded members once they are re-admitted into the group. However, it also leads to some retaliation by low-productivity members. A particularly worrisome aspect of exclusion is that punished group members are stigmatized and have a higher probability of facing exclusion again. We discuss implications of our findings for penal systems and their capacity to rehabilitate prisoners.
10419/240447
Keywords: Graue Literatur; ostracism; social dilemma; theft; rehabilitation; heterogeneous groups